Differential Predictive Effect of Self-Regulation Behavior and the Combination of Self- vs. External Regulation Behavior on Executive Dysfunctions and Emotion Regulation Difficulties, in University Students - de la Fuente, Jesús; Martínez-Vicente, José Manuel; Pachón-Basallo, Mónica; Peralta-Sánchez, Francisco Javier; Vera-Martínez, Manuel Mariano; Andrés-Romero, Magdalena P. (Frontiers in Psychology, 2022)
The aim of this research was to establish linear relations (association and prediction) and inferential relations between three constructs at different levels of psychological research --executive dysfunction (microanalysis), self-regulation (molecular level) and self- vs external regulation (molar level), in the prediction of emotion regulation difficulties. We hypothesized that personal and contextual regulatory factors would be negatively related to levels of executive dysfunction and emotion regulation difficulties; by way of complement, nonregulatory and dysregulatory personal and contextual factors would be positively related to these same difficulties. To establish relationships, we used a retrospective, ex post facto design, where 298 university students voluntarily participated by completing standardized self-reports. Linear and structural correlational, predictive analyses were performed, as well as inferential analyses. Results were consistent and validated the proposed hypotheses, for both association and prediction. The most important result refers to the discriminant value of the five-level combination heuristic for predicting Executive Funtion and External (contextual) Dys-Regulation. In conclusion: (1) both personal and contextual regulation factors must be analyzed in order to better understand the variation in executive functions and emotion regulation difficulties; (2) it is important to continue connecting the different levels of the constructs referring to self-regulation, given their complementary role in the behavioral analysis of regulation difficulties.